The Use of Forest Resources versus Economic Growth in Brazil: is possible to reach a balance? - Carlos Bacha (European Regional Science Association (ERSA), 2011)
This article analyzes how forest resources have been used in Brazil since 1930, in an attempt to prove two hypotheses. The first hypothesis is that the destruction of our forests and the unsustainable use of the remaining forests have always been linked to the developmental policies adopted in the country. These policies, in their turn, have been based on the main economic models in vogue at the time. The second hypothesis is that, even recognizing the ineffectiveness of only adopting policies to regulate and control deforestation, policy-makers have only broadened and sophisticated this type of policy over time (through the forest legislation), without creating meaningful economic incentives to preserve and conserve forest resources. To prove these hypotheses, this article contains a discussion of the importance of forests to a nation and emphasizes that Brazil is destroying them on a large scale in different intensities among the Brazilian states. The latter has taken place despite the deforestation cannot be justified by the need of new farming land in most of Brazilian states. Finally, the article discusses some policies that allow the rational use of forest resources in Brazil without hindering the growth of other economic activities and considering the Brazilian states differences.
Keywords: 330